PER3 variable number tandem repeat (VNTR) polymorphism modulates the circadian variation of the descending pain modulatory system in healthy subjects - Carvalho, Fabiana; Pedrazzoli, Mario; Gasparin, Assunta; dos Santos, Franciele; Zortea, Maxciel; Souza, Andressa; da Silva Lucena Torres, Iraci; Fregni, Felipe; Caumo, Wolnei (Scientific reports, 2019)
We evaluated the circadian pattern of variation of the descending pain modulatory system (DPMS) using a conditioned pain modulation (CPM) paradigm according to the variable-number tandem-repeat (VNTR) of the clock gene PER3 polymorphism. We assessed the relationship between the genotypes PER3 4/4 and PER3 5/5 and the temporal pattern of variation across the day using the following measures: the heat pain threshold (HPT), the cold pressure test (CPT), and the serum levels of BDNF and S100-B protein. The ∆-values (from afternoon to morning) of these measures were used for the analysis. The circadian phenotype was according to the mid-point sleep time established by the Munich ChronoType Questionnaire (MCTQ). We included 18 healthy volunteers (15 women) ages 18 to 30. A Generalized Linear Model (GLM) revealed a significant difference in the ∆-CPM-task between Per3 4/4 and Per3 5/5 genotypes, with means (SDs) of −0.41 (0.78) vs. 0.67 (0.90) (χ 2 = 7.256; df = 1′ P = 0.007), respectively. Both sleep deprivation of at least 2 h/day (B = −0.96, 95% confidence interval (CI) = −1.86 to −0.11)) and the ∆-S100-B protein (−0.03, 95% CI = −0.06 to −0.02) were negatively correlated with the ∆-CPM-task, while the ∆-BDNF was positively correlated with the ∆-CPM-task (0.015, 95% CI = 0.01 to 0.03). We observed a difference in the ∆-CPT between PER3 4/4 and PER3 5/5 (0.11 (4.51) vs. 4.00 (2.60), respectively) (χ 2 = 22.251; df = 1 P = 0.001). These findings suggest that the polymorphism of PER3 5/5 is associated with a decrease in the inhibitory function of the DPMS over the course of the day. However, sleep deprivation is an independent factor that also reduces the inhibitory function of the DPMS, regardless of the PER3 VNTR polymorphism.